Impact of Traditional Environmental Management Measures and Ecological Product Diversification on MSME Performance: Evidence of the Batik Industry in Central Java, Indonesia - Widjajanti, Kesi; Sugiyanto, Eviatiwi Kusumaningtyas (Jurnal Manajemen Bisnis, 2023)
Research aims: This research aims to investigate the influence of traditional environmental management practices on corporate performance and determine the mediating role of ecological product diversification in this regard.Design/Methodology/Approach: To achieve these objectives, a research design was developed and tested using a sample of 138 micro, small and medium enterprises (MSMEs) operating in the batik industry in Central Java, Indonesia. Observation data were then analyzed using Structural Equation Modeling (SEM) utilizing Amos software.Research findings: The analysis results demonstrated that traditional environmental management and ecological product diversification had a direct positive impact on the performance of small and medium enterprises. However, these results did not confirm the mediating role of ecological product diversification.Theoretical contribution/Originality: This study provides convincing evidence regarding the impact of environmentally friendly product diversification on MSME performance. Therefore, MSMEs, especially those operating in the batik industry, are encouraged to diversify environmentally friendly products to increase competitiveness and adapt to people's concern for the environment in the current era (green economy). Practitioners/Policy implications: It is acknowledged that the overall results obtained from this research provide a significant contribution to the understanding of the importance of environmental management practices and environmentally-friendly product diversification to increase business efficiency in the context of MSMEs.Research limitations/Implications: This study had a limited scope and only covered the Central Java region. Subsequent research can further expand the scope of the research field.